AÃ‡ÃƒO DE ALGUNS INSETICIDAS SOBRE A BROCA DAS CUCURBITÃCEAS Margaronia nitidalis (CRAMER, 1782) - Botelho, P. S. M.; Nakano, O.; Rodella, R. J. (REVISTA DE AGRICULTURA, 2015)
AÃ‡ÃƒO DE ALGUNS INSETICIDAS SOBRE A BROCA DAS CUCURBITÃCEAS Margaronia nitidalis (CRAMER, 1782)